(untitled) (Semiárida, 2025)
Mechanical tillage, used as a rejuvenation practice in a degraded “weeping lovegrass” pasture, breaks up soil compaction, improves aeration, and increases water infiltration. This intervention also fragments aged tussock, generating a new and better spatial distribution of tillers, filling in empty spaces, and thus improving cover. The objective of this study was to evaluate the rejuvenation of a degraded weeping lovegrass (PLl) pasture using a chisel plow and subsequently compare its effect on forage production in successive growing seasons. The trial was conducted in the Agricultural Experimental Station of INTA Anguil, La Pampa, on a PLl pasture planted in the 1960s. The pasture was in an advanced state of degradation, characterized by high heterogeneity, alternating areas with large, aged tussock plants with others of a pasture-like pasture with small, weak tussocks. This condition was compounded by the presence of other species, mostly perennial forage grasses (GF) and non-forage grasses (GNF). In July 2021, a 9-tine chisel plow spaced 45 cm apart was used over half the plot, with a tillage depth of 30 cm. The trial (2021 – 2024) was established with two treatments: chisel plow (CC) and non-chisel plow (SC). Vegetation sampling sites were fixed throughout the trial period. Five closed cages were used for this purpose for each treatment. Plant density was determined at the beginning and end of the trial, as well as the biomass produced in each of the three growing seasons. The results showed that, except for the first growing season, where no significant differences were detected, the CC treatment outperformed the control in PLl biomass production by 80 and 90 % during the second and third seasons, respectively. Tillage with a chisel plow improved plant density and productivity of weeping lovegrass, demonstrating its potential as a tool for restoring degraded pastures.